1×5 Microfluidic optical switch using double drives. Issue 21 (15th December 2021) - Wan, Jing; Yuan, WenZhi; Chen, YiJing; Zhu, Xu; Guo, MingRui; Xu, Peng
Abstract : Here a 1×5 microfluidic optical switch using double drives is proposed. It has a simple structure and ignorable polarization dependent loss. First, the switch with the straight waveguide structure is discussed. Then, various optimization schemes are used, where the oblique waveguide structure and the method of constant refractive index ratio of interface significantly reduce the insertion loss. The final optimization results show that the 1×5 optical switch has smaller insertion loss and crosstalk than general optical switches. For 1550 nm wavelength, the insertion losses of five exit ports are 0.27 dB ∼ 0.47 dB, and the crosstalks are −24.8 dB ∼ −66.5 dB. For 1310 nm wavelength, the insertion losses are 0.13 dB ∼ 0.23 dB, and the crosstalks are −25.6 dB ∼ −70.8 dB. Our work can promote the application of microfluidics in the optical communication and provide a reference for finding waveguide optical switches with low insertion loss.